Ultra Low-Conductivity Water by Electrophoretic Ion Exclusion - Haller, Wolfgang (J Res Natl Bur Stand A Phys Chem, 1960)
Ultra low-conductivity water has been prepared by recirculating it through an electric field of 1,000 volts/centimeter maintained between two ion selective membranes. It was possible to obtain consistently water with an electrical conductivity below the lowest values reported in the literature. The lowest conductivity value which could be reached was 0.039 × 10(−6) ohm(−1) cm(−1) at 18 °C, indicating an ionic impurity content of only one third of the minimum previously reported. This corresponds to the conductivity of a sodium chloride solution at a concentration of 0.0010 parts per million.